Epigenetic constraints and enhancer innovation link neuronal plasticity to evolutionary adaptation - Andrea Millán-Trejo; Carlos Mora-Martínez; Adrián Tarazona-Sánchez; Carla Lloret-Fernández; Rafael Alis; Antonio Jordán-Pla; Arantza Barrios; Nuria Flames (Proceedings of the National Academy of Sciences, 2026)
How nervous systems balance the generation of robust neuron types with gene expression plasticity mechanisms and how these processes impact cell-type evolution are unknown. Here, we use Caenorhabditis species to study neuron-type robustness, plasticity, and evolution, using VC4 and VC5 cholinergic motoneuron types as models. In Caenorhabditis elegans , we found that epigenetic silencing through histone 3 lysine 9 methylation (H3K9me) is necessary to suppress the expression of the serotonin reuptake gene mod-5/ Sert and a serotonergic phenotype in these cells. In contrast, we observed that VC4 and VC5 neurons in the Angaria group of Caenorhabditis species have evolved an intense serotonergic staining. This phenotype is caused by the emergence of a new enhancer in the mod-5/ Sert locus, which has been recruited to the ancestral neuron-type gene regulatory network. Enhancer transfer from C. angaria is sufficient to impose a constitutive serotonergic fate in C. elegans . Remarkably, acquiring this new trait modulates egg-laying responses to high levels of exogenous serotonin, which can be found in specific nematode environments. Finally, we found that the repression of the serotonergic fate in C. elegans VC4 and VC5 neurons is indeed a plastic trait that can be adjusted in specific environmental growth conditions to elicit egg-laying behaviors similar to those observed in Angaria species. Our work uncovers a dual regulatory paradigm: Epigenetic constraints harmonize neuron-type robustness and plasticity, while enhancer co-option enables evolutionary innovation. This mechanistic plasticity directly links regulatory adaptation to behavioral diversification.